2015
DOI: 10.1039/c5cc05922d
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of DNA methyltransferase activity by transcription-mediated duplex-specific nuclease-assisted cyclic signal amplification

Abstract: We develop a sensitive fluorescence method for DNA methyltransferase (MTase) assay based on T7 RNA polymerase-mediated transcription amplification and duplex-specific nuclease (DSN)-assisted cyclic signal amplification. This method exhibits excellent specificity and high sensitivity with a detection limit of 0.015 U mL(-1), and it may be further applied for the screening of antimicrobial drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In this study IC50 has been found to be 3.1 µM which indicates that this is a promising method to screen the inhibitor effects of drugs on MTase [56,57].…”
Section: Fig 3 Msssi Methyltransferase Inhibition Assaymentioning
confidence: 66%
See 1 more Smart Citation
“…In this study IC50 has been found to be 3.1 µM which indicates that this is a promising method to screen the inhibitor effects of drugs on MTase [56,57].…”
Section: Fig 3 Msssi Methyltransferase Inhibition Assaymentioning
confidence: 66%
“…To check the validity of our method in screening the inhibitors of M.SssI, we have employed Gentamicin as an inhibitor model [56]. We have evaluated the inhibitor effects by incubating DNA-Ag/Pt NCs and M.SssI MTase and SAM with different doses of Gentamicin (Fig.…”
Section: Fig 3 Msssi Methyltransferase Inhibition Assaymentioning
confidence: 99%
“…DSN is widely used in fulllength enriched cDNA normalization, 18,19 construction of normalized RNA-seq libraries for next generation sequencing 20,21 and molecular biology. [22][23][24] Very recently, based on excellent selectivity in digestion of DSN, the Ye group has established a new signal-amplifying mechanism, which was duplex-specific nuclease signal amplification (DSNSA), for highly sensitive detection of miRNA. 25 From then on, several miRNA detection methods based on DSN have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…142 However, traditional methods for DNA methyltransferase activity assay rely on radioisotope materials. 109 Therefore, radioisotope-free approaches have been developed, including electrochemical, [109][110][111][112][113][114][115][116][117][118][119] electrochemiluminescence, [120][121][122] photo-electrochemical, 123 fluorometric, [124][125][126][127][128][129][130][131][132][133][134][135] surface-enhanced Raman scattering (SERS), [136][137][138] and circular dichroism (CD) spectroscopy, 139 and surface plasmon resonance 140 based DNA methyltransferase measurement techniques have recently been proposed as summarized in Table 2 to realize simple, quick and easy monitoring.…”
Section: Dna Methyltransferase Activitymentioning
confidence: 99%